Kinematics and kinetics of barefoot, shod, and spiked sprinting during acceleration and at maximum speed - Fuchs, P. X.; Hsiao, H.-W.; Han, Y.-.; Uzomba, C. G.; Nagahara, R. (ISBS Proceedings Archive: Vol. 42: Iss. 1, 2024)
The purpose of this study was to analyze biomechanical differences between footwear conditions during acceleration and sprinting at maximum speed. Competitive sprinters (n=17) completed 60-m sprints barefoot, in running shoes, and in spiked sprint shoes in a randomized order. Fifty-four force plates (1000 Hz) obtained ground reaction forces over 50 m. Main effects between phases were found in all nine spatiotemporal and kinetic variables (p<0.001, partial eta2=0.728). Differences in braking and propulsive forces and impulses between footwear conditions seemed larger during acceleration (p<0.001, partial eta2=0.38-0.57) than at maximum speed (p<0.15, partial eta2=0.11-0.38). The findings underlined the importance of kinetic analysis across different sprint phases. Footwear effects on forces and associated joint loads may be considered in the management of overload injury risks.